2010
DOI: 10.30535/mto.16.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Mode, Harmony, and Dissonance Treatment in American Folk and Popular Music, c. 1920–1945

Abstract: In American folk and popular music, dissonance frequently functions in ways that cannot be explained by conventional tonal theory. Two types of dissonance—the dropping and hanging thirds—function outside of classical norms, and within the framework of a mode built around the tonic triad that either transposes or remains in place with changes of harmony. The interaction between the mode and harmony influences the large-scale structure of a strophe or other section and the perception of its tension and resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The large-scale harmonic structure in Johnson's blues songs follow, more or less closely, the 12-bar blues pattern that became one of the most common (if not the most common) in the decades that followed . It differs a little from the pattern Stoia gives as the ‘Standard 12-bar Blues’ in that bar 12 is articulated by level V and bar 10 is articulated by level IV (Stoia 2010, para 3). Johnson will sometimes substitute I for IV in bar 2 as he does in the first verse but not subsequent verses of ‘Kindhearted Woman’ 31 .…”
Section: The Music Of Robert Johnsonmentioning
confidence: 84%
See 2 more Smart Citations
“…The large-scale harmonic structure in Johnson's blues songs follow, more or less closely, the 12-bar blues pattern that became one of the most common (if not the most common) in the decades that followed . It differs a little from the pattern Stoia gives as the ‘Standard 12-bar Blues’ in that bar 12 is articulated by level V and bar 10 is articulated by level IV (Stoia 2010, para 3). Johnson will sometimes substitute I for IV in bar 2 as he does in the first verse but not subsequent verses of ‘Kindhearted Woman’ 31 .…”
Section: The Music Of Robert Johnsonmentioning
confidence: 84%
“…The difficulties presented by Weisethaunet's arguments go much of the way towards explaining why recent theoretical work on the blues and blues-related musics has largely ignored the issues he raises. The most important work in this regard is that of Nicholas Stoia (2010, 2013), whose thorough and rigorous work on blues music uses methods closely related to those dominating analytical approaches to music in the classical tradition 4 . Alongside such approaches Stoia does cite the work of ethnomusicologists such as David Evans and Gerhard Kubik, a fact that suggests some sensitivity to the kinds of issues highlighted by Weisethaunet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors further go on to describe a "neutral" or "blue note" third as a blending between the two. It has long been observed that the blues artist frequently slurs between major and minor thirds (Jones, 1951;Kubik, 1999Kubik, , 2005Kubik, , 2008Niles, 1972;Stoia, 2010;von Hornbostel (as cited in Kubik, 2008, p. 16); Weisethaunet, 2001). Temperley et al (2017) postulate that the distributions of two distinct auditory targets (like Figure 3) separated by a half step should have an additive overlap between tones, but the resultant curve should present as two peaks with a definite "valley" between them, if the two notes were sung as independent vocal projections.…”
Section: The "Neutral" Third and Tritonementioning
confidence: 99%
“…Stoia suggests that the progression ‘emphasizes the cadence by approaching the final tonic from both its upper and lower dominants' (, p. 209). See also Stoia (), para. 16 and n. 18.…”
mentioning
confidence: 99%